Fitotoxicidade e metaboloma de extratos foliares aquosos de espécies do cerrado - Vargas, Sharmely Hilares (2020)
Plants with allelopathic potential are promising in the sustainable control of weeds and the chemical characterization of the compounds is important in identifying the bioactive potential. This study aimed to perform the chemical characterization from the evaluation of the phytotoxic activity of medicinal species from the Cerrado of Mato Grosso. For this, the work was divided into two chapters. In the first chapter, a phytotoxic evaluation of the leaves of 12 species was carried outDavilla elliptica, Tocoyena formosa,Combretum laxum, Himatanthus obovatus, Rudgea viburnoides, Diteryx alata, Curatella americana, Qualea grandiflora, Aspidosperma macrocarpon, Caryocar brasiliense, Tibouchina candolleana e Miconia albicans,collected in the municipality of Chapada dos Guimarães / MT. The aqueous extract for each species was obtained from the grinding in a blender of 50 g of fresh leaves with 500 mL of distilled water. Germination bioassays and initial development of lettuce seedlings (Lactuca sativa L.) were carried out in different concentrations of the extracts: 0, 25, 50, 75 and 100% obtained by dilution with distilled water. The results indicate that the allelopathic effect varied according to the concentration of the aqueous extracts and the donor species. The leaf extracts of the species T. formosa, H. obovatus, R. viburnoides and T. candolleana presented low allelopathic response index. The species C. laxum, D. elliptica, C. brasiliense and Q. grandiflora had the greatest potential for phytotoxic effect on the germination of lettuce seeds. From these results, a preliminary evaluation of the chemical composition and degree of toxicity in nematodes of the extracts of the species with the greatest allelopathic effect (C. laxum, D. elliptica, C. brasiliense and Q. grandiflora) was carried out. The technique of infrared spectroscopy (IVTF) confirms the presence of functional groups with allelopathic effect such as alkanes, alkenes, phenols and aromatics. Thin layer chromatography identified the presence of classes of organic compounds such as terpenes, flavonoids, phenols and alkaloids in the leaves of the species evaluated. In the second chapter, the metabolic profile of the leaves of the species Davilla elliptica (Dilleniaceae), Combretum laxum (Combretaceae), Caryocar brasiliense (Caryocaracea) and Qualea grandiflora (Vochysiaceae) was carried out. Initially, the allelopathic effect of the extracts on lettuce seeds was confirmed. Then, the chemical characterization of the extracts was performed using the 1H NMR technique. 69 metabolites were identified for D. elliptica, 74 for C. laxum, 66 for C. brasiliense and 65 for Q. grandiflora, being mainly primary compounds. The metabolic profile of the leaves suggests that the species are different both qualitatively and quantitatively. Multivariate analyzes of hierarchical and discriminant grouping indicate that there is a similarity in the chemical composition and in the allelopathic effect between the species C. laxum and Q. grandiflora, possibly due to the phylogenetic proximity of the species with respect to order.